عوامل تدهور وانهيار الامامة الاباضية في عمان - فوزي, فاروق عمر (مجلة الآداب, 1977)
Keywords: Imamat – Oman

The imamate tradition of Oman - Wilkinson, John Craven (Cambridge University Press, 1987)
At the core of this book is an attempt to explain a conflict in Oman in the 1950s and 1960s between two claimants to authority: the Imam of the Ibadi sect and the Sultan.
Keywords: Imamat – Oman